Time for Reflection: The Balance between Repetition and Feedback in Resuscitation Training—A Randomised Controlled Trial. (25th October 2015) - Krogh, Kristian; Pilegaard, Morten; Eika, Berit
Abstract : Background . The simulation literature widely agrees that the reflective learning phase after the simulation is equal to or perhaps of even greater importance than the actual simulated scenario in ensuring learning. Nevertheless, advanced life support (ALS) tends to have many simulated scenarios followed by short feedback sessions. The aim of this study was to compare the ability of two groups of novice learners to stay adherent to the ALS guidelines in their provision of ALS after they had received either 8 or 12 simulated resuscitation scenarios, both in 4 hours. Methods . This study was a randomised controlled trial. Participants were either randomised to the control group with 12 scenarios (15 minutes per scenario) with 5 minutes of feedback or the intervention group with 8 simulations (15 minutes per scenario) with 15 minutes of feedback. Results . There was no statistically significant difference in test scores between the intervention group and control group in the 1-week retention test( p = 0.59 ) and the 12-week retention test( p = 0.43 ) .   Conclusion . This study suggests that the lower number of repetitive ALS simulation scenarios does not diminish learning when the feedback is equally prolonged to ensure sufficient time for reflection.